Consumer roles and values in selfie experience: a case of Korean young consumers - Kwon, Yoo Jin; Kwon, Kyoung Nan (Qualitative Market Research, 2018)
Purpose: The purpose of this study is to understand the values consumers pursue and roles consumers partake in selfie practice. Design/methodology/approach: A qualitative research method was adopted. In-depth interviews were conducted with selfie enthusiasts. Data were analyzed with grounded theory approach. Findings: Diverse activities and reflections pertaining to selfies were analyzed, which uncovered three consumer roles departmentalized and the nine values that selfie practice generates for consumers. The three roles are subject, photographer and user of selfies, and the roles are orchestrated together or selectively performed if necessary. In consequence of the interplay of performances and expectations of the roles, consumers pursue and gain four collaboratively created values and five individually created values. Originality/value: Findings of the study expand the understanding of values of selfie practice and consumer roles in Web 2.0.
Keywords: Consumer roles; Digital self; Hybrid space; Selfie; Values